Faith-Based Transformational Leadership in the Digital Age: A Case Study of Social Media-Driven Educational Fundraising for Orphans in Indonesia - Siswadi Siswadi; Asdlori Asdlori; Muhammad Masruri (Nazhruna: Jurnal Pendidikan Islam, 2026)
This study investigates the transformational leadership practices of the chairman of the Al-Mujahidin Cilacap Orphanage in leveraging social media for educational fundraising targeting underprivileged children. Employing a qualitative phenomenological approach, data were collected through in-depth interviews, participatory observation, and document analysis. The data were interpreted using the Miles and Huberman interactive model, encompassing data reduction, display, and conclusion drawing. This study aims to analyze the role of belief-based transformational leadership in deploying educational fundraising strategies for orphans, and to examine how the values of belief, transformative vision, and the influence of ideal leaders are constructed. The findings identify six strategic leadership actions that contribute to effective social media–based educational fundraising, among others: establishing a digital communication team, disseminating fundraising content across personal and institutional platforms, mobilizing internal educational leaders within the foundation’s network, collaborating with community influencers, cultivating and maintaining donor relationships via social media, and diagnosing key enabling and constraining factors. This research provides improvements to belief-based digital leadership strategies, including the use of digital influence to mobilise educational philanthropy. It creates a framework for non-profit leaders and Islamic philanthropic institutions.